2018
DOI: 10.3233/wor-182728
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review of the incentives for a prolonged work life after pensionable age and the importance of “bridge employment”

Abstract: Attitudes and behavior according to a prolonged work life could be summarized as dependent on good health, a financial gain in combination with flexible alternative working conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 74 publications
1
39
0
Order By: Relevance
“…Work demands may likewise push the worker out of the labour market. A scoping review identified physical and cognitive demands at work as barriers for prolonged work participation after pensionable age [2], these findings are supported by another review that showed that physical work demands and work pressure were related to early retirement [13]. Qualitative findings confirm that particularly work pressure [13,14] and to a lesser extent physical work demands [13] contribute to early retirement.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…Work demands may likewise push the worker out of the labour market. A scoping review identified physical and cognitive demands at work as barriers for prolonged work participation after pensionable age [2], these findings are supported by another review that showed that physical work demands and work pressure were related to early retirement [13]. Qualitative findings confirm that particularly work pressure [13,14] and to a lesser extent physical work demands [13] contribute to early retirement.…”
Section: Introductionmentioning
confidence: 82%
“…Various factors influence workers' retirement intentions and behaviour [1,2] and they have been categorised into Push, Pull, Jump, Stuck, and Stay (e.g., Andersen, Jensen [3]). Push refers to factors pushing the worker involuntary out of the labour market such as ill health or adverse working conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This entails a gender inequality (SDG 5), since voluntary care is more common among women. As a result, women also get lower retirement pensions (Björklund, Brushammar, Bjursell, Nystedt, & Nilsson, 2018). Moreover, prolonged employment after retirement age is not self-evident for every employee who wants or needs to, since this possibility is most often reserved for the highly educated (Bjursell, Nystedt, Björklund, & Sternäng, 2017), i.e.…”
Section: Sustainability In Research the Last Five Yearsmentioning
confidence: 99%
“…SDG 10. For those without possibilities for prolonged employment with their original employer, staffing agencies offer jobs for retirees, but often for lower pay than before (Björklund et al, 2018), which relates to SDGs 8 and 10.…”
Section: Sustainability In Research the Last Five Yearsmentioning
confidence: 99%